University, dictatorship and school movements in Argentina. Cordoba 1966-1974 (2014)
The purpose of this article is to analyze the situation of the National University of Cordoba, from the so-called “Argentinian Revolution” until the death of Juan Domingo Perón, Focusing our attention on the socio-political situation of the period which was crossed by student movements and changes in regulations for higher education that have impacted on autonomy and the university government.